Lateral variation in structural style of mountain building: controls of rheological and rift inheritance. (16th December 2013) - Jammes, Suzon; Huismans, Ritske S.; Muñoz, Josep Anton
Abstract Many mountain belts exhibit significant along‐strike variation in structural style with changes in the width of the orogen, the geometry and kinematics of the crustal‐scale thrust system, and the degree of partitioning between pro‐ and retro‐wedge deformations. Although the main factors controlling first‐order structural style are understood, the cause of these lateral variations remains to be resolved. Here we focus on the Pyrenees, characterized by significant lateral variation in structural style with a thrust system involving more and thinner thrust sheets in the eastern section than in the western part. Similarly, the prior Mesozoic rifting event was characterized by significant lateral variation in structure. We integrate available geological and geophysical data with forward lithospheric scale numerical models. We show that lateral variation in crustal strength attributed to inherited Variscan crustal composition accentuated during Mesozoic rifting explains the variation in structural style observed during Pyrenean mountain building.